2021
DOI: 10.1101/2021.11.05.467326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internal state dependent control of feeding behaviour via hippocampal ghrelin signalling

Abstract: Hunger is an internal state that not only invigorates behaviour towards feeding, but also acts as a contextual cue for the higher-order control of anticipatory feeding-related behaviour. The ventral hippocampus is a brain region important in encoding context, but how internal contexts such as hunger are represented in hippocampal circuits is not known. Pyramidal neurons in the ventral hippocampus, and in particular within the ventral CA1/subiculum border (vS) express the receptor for the peripheral hunger horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 101 publications
2
3
0
Order By: Relevance
“…Activity of dHPC neurons, and especially those projecting to NAc, thus seems to mirror the activity within NAc: Inhibition of NAc D1R medium spiny neurons (MSNs) has been observed during lick behavior 74,92,93 and was shown to be both necessary 93,94 and sufficient 93,95 for consummatory licking. We found that the origin of these signals may be localized upstream, similar to recent findings of an inhibitory permissive drive for licking in ventral HPC (vHPC) projections to the NAc 74,75 and that inhibiting these projections facilitates licking 74 . This suggests a similar involvement of dHPC-and vHPC-accumbens projections for consummatory licking.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Activity of dHPC neurons, and especially those projecting to NAc, thus seems to mirror the activity within NAc: Inhibition of NAc D1R medium spiny neurons (MSNs) has been observed during lick behavior 74,92,93 and was shown to be both necessary 93,94 and sufficient 93,95 for consummatory licking. We found that the origin of these signals may be localized upstream, similar to recent findings of an inhibitory permissive drive for licking in ventral HPC (vHPC) projections to the NAc 74,75 and that inhibiting these projections facilitates licking 74 . This suggests a similar involvement of dHPC-and vHPC-accumbens projections for consummatory licking.…”
Section: Discussionsupporting
confidence: 87%
“…Contrasting this consumption-related inhibition, we found appetitive lick-related dHPC→NAc excitation and optogenetic induction of lick-related behaviors. This dichotomy likely reflects previously described differences in the NAc's role for consummatory and appetitive behaviors 61 : vHPC→NAc activity was shown to increase during active food investigation 75 and around the time of lever pressing to obtain a reward 96 , while optogenetic stimulation of this projection facilitated nose poke and lever pressing behaviors 31,34 . Given that optogenetic stimulation of D2R MSNs in the NAc shell was also found to produce repetitive jaw movements 97 , it is likely that D1R and D2R MSNs, both of which are targeted by HPC axons 30,98,99 , might play dichotomous roles in appetitive and consummatory behaviors 30,100 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The recorded behavioural sequences allowed analysing motivation transition likelihoods 10,11 (Figure 12H). As expected from the efficient organization of a small number of multi-trial blocks per hour, transition types within the foraging environment were most frequent (food-to-food, food-to-drink, drink-to-drink and drink-to-food).…”
Section: Test Measurement Of Discretized Motivational Transitionsmentioning
confidence: 99%
“…On a slower timescale, a probabilistic behavioural satiety sequence of feeding-grooming-resting, occurring over the course of an hour has been described in rodents and crayfish 8,9 . Transitions between sequential motivated behaviours in the home cage environment are seldom measured at a high temporal resolution [10][11][12] . This may be because motivational switching can be highly disordered in the home cage where the goal objects are constantly accessible.…”
Section: Introductionmentioning
confidence: 99%